Multi-omics analysis reveals Lactobacillus and Indolelactic acid involved in small intestinal adaptation of piglet with short bowel syndrome. - Wang, Weipeng; Lu, Ying; Wu, Bo; Peng, Shicheng; Cai, Wei; Xiao, Yongtao (Nutrition & Metabolism, 2025)
Background: Short bowel syndrome (SBS) is a condition characterized by malabsorption that occurs when a patient loses a significant amount of bowel length or function, often necessitating lifelong parenteral nutrition support. This study utilized multi-omics analysis to investigate alterations in gut microbiota, metabolism, and transcriptome during the progression of intestinal adaptation in SBS using a piglet model. Methods: We established a model of SBS in Bama mini piglets by performing a 75% jejunoileal resection. Fifteen piglets were randomized into EN, PN, and PN-SBS groups. Fecal samples were collected for 16 S rRNA gene-based microbiota analysis. Ileal mucosa and serum were collected for untargeted liquid chromatography-mass spectrometry. Transcriptomic analysis on ileal mucosa was performed. Results: The PN-SBS model was established in the newborn piglets. A significant decrease in species-level diversity was observed in piglets with SBS, accompanied by alterations in their microbiome compositions. The beneficial anaerobes from Bacillota and Bacteroidota were depleted while microorganisms from Verrucomicrobiota and Fusobacteriota were enriched in feces from SBS piglets. The dysregulation of metabolites and metabolic pathways was observed in the metabolic profiles of ileal mucosa and serum in SBS piglets. Indolelactic acid (ILA) levels were found to be reduced in the ileal mucosa and serum of SBS piglets. Transcriptomic analysis revealed an extensive functional alteration in SBS, primarily manifested as metabolic changes and intestinal proliferation. The multi-omics analysis revealed that the decreased abundance of Lactobacillus may result in a diminished production of their metabolite ILA, thereby influencing intestinal proliferation and anti-inflammatory responses. Conclusion: Disrupted homeostasis of gut microbiota, metabolism, and transcriptome were reported in the SBS piglets. Multi-omics analysis demonstrated Lactobacillus and its metabolite ILA may be involved in small intestinal adaptation of SBS. These alterations may contribute to the proinflammatory state and the delay of intestinal adaptation in SBS, which in turn provide promising targets for therapies.